E-Complaints For SG (Social Grants) : Upaya Preventif dalam Penanggulangan Tindak Pidana Korupsi di Tengah Pandemi - Sri Putri Amalia Jamal; Sahrana; Desi Fitriyani (UKM Lembaga Penalaran dan Penulisan Karya Ilmiah Fakultas Hukum Universitas Hasanuddin, 2021)
Abstract The problem of distributing Covid-19 relief funds in Indonesia, apart from not being on target, has also been corrupted. At the normative level, penalties for convicted corruption cases have been regulated, including the death penalty that has been established. However, it does not seem to be sufficient as a repressive measure. Therefore, certain measures are required to prevent the corruption. This research is conducted to find out how the corruption occurs in the funds’ distribution. In addition, it is also expected to become a forum for the public to file complains if there is a gap regarding the distribution of the funds which indicates corruption. This study is carried out through a normative law research, with literature study. The method used is conceptual approach and case approach. To deal with the existing problems, the writer offers a concept in the form of a website,